Formation of digital literacy components of future teachers in the course of studying the university-wide discipline “Digital Technologies in Education” - Natalya I. Isupova; Tatyana N. Suvorova (RUDN Journal of Informatization in Education)
Problem statement . Development of informatization of education occurs under the influence of large-scale penetration of digital technologies into all spheres of modern society. Considering this influence, it becomes important to identify and take into account the current level of digital literacy of future teachers and, based on its analysis, develop a scientific and methodological justification for determining the structure and content of the discipline destined for preparing future teachers to work in the context of digital transformation of education. The article presents a study aimed at substantiating the need for a differentiated approach to teaching the discipline “Digital Technologies in Education” studied by students of the pedagogical direction of training within the framework of bachelor’s degree program. Methodology . Theoretical and methodological analysis and generalization of fundamental scientific works on the research problem and processing of testing results are used. Experimental work is carried out on the basis of Vyatka State University. The pedagogical experiment involves 111 bachelors in the field of study 44.03.05 “Pedagogical education (with two training profiles)”, profile “Subject training. Teaching and education technologies”. A differentiated approach to organizing the study of the discipline “Digital Technologies in Education” is considered as an innovative method for developing digital literacy of future teachers. At the stage of diagnostics and assessment of the formation of digital literacy of bachelors, an original test is used, aimed at identifying the level of formation of five components of digital literacy of future teachers: information, computer, communication and media literacy, as well as attitudes towards technological innovations. The Pearson’s χ2 (chi-square) criterion is used as a statistical processing method. Differentiation of the content of the discipline and division of students into subgroups occurs on the basis of an analysis of the results of input diagnostics, during which the most acute deficiencies in the formation of one of the five components of the student’s digital literacy are identified. Results . Statistically significant differences in the qualitative changes that occurred in the level of the digital literacy index of students in the experimental group trained in accordance with the proposed approach were revealed (χ2 = 9.570; α 0.05). Conclusion . The use of a differentiated approach to studying the discipline “Digital Technologies in Education” helps to increase the level of digital literacy of future teachers. This approach, based on identifying and taking into account the most acute deficiencies in the development of digital literacy components, will allow to increase the students’ own digital literacy index, as well as to form their readiness to use digital educational tools in future pedagogical activities in order to increase the level of digital literacy of schoolchildren.